Some Factors Affecting the Breakdown Strength of Solid Dielectrics: A Short Review - Danikas, M.; Vardakis, G. E.; Sarathi, R. (Engineering, Technology & Applied Science Research, 2020)
This paper refers to some factors affecting the breakdown strength of solid insulating materials. Solid insulating materials play a most important role in the high voltage industry. Factors, such as area effect, crystallinity, impregnation with liquids, temperature, the role of interfaces and mechanical stressing, are investigated and commented upon.